Workload and Leadership in Indonesian Hospitals: Implications for Performance - Firasghani, Muhammad Almy; Andiani; Willy Anugroho (International Journal Administration, Business & Organization, 2026)
The sustainability of hospitals in Indonesia is increasingly challenged by structural workload pressures and managerial leadership effectiveness, particularly within the post-pandemic and universal health coverage environment. Although prior empirical studies have examined workload and leadership independently, limited research integrates these determinants within a unified hospital performance framework. This study aims to systematically review empirical evidence on how workload and leadership influence hospital performance through job satisfaction in Indonesian hospital settings. A systematic literature review was conducted on peer-reviewed articles published between 2019 and 2025. Fifteen eligible studies were analyzed using thematic synthesis. The findings demonstrate that excessive workload consistently reduces job satisfaction and increases turnover intention, whereas supportive and participative leadership enhances employee morale and performance stability. Job satisfaction functions as a mediating governance mechanism linking organizational conditions to institutional performance outcomes. This study contributes to hospital management literature by positioning job satisfaction as a strategic performance indicator and proposing a monitoring-oriented managerial framework to strengthen organizational resilience in Indonesian hospitals.